Language arts in American middle schools, 1980-83 : - Steele, Cheryl A. (My University, 1984)
It was noted that many of the items of interest to middle school language arts educators were presented and published in sources not readily available for these teachers.

Analyses of the data revealed a definite emphasis on basic skills in language arts as well as an effort to expand the scope of the language arts to meet specific transescent needs. Innovative programs and teaching approaches attempted to implement the basic skills approach in new and measurable ways and also create a desire in students for learning. Research on the cognitive development of transescents was identified as a major influence on curricula, teaching programs, methods, and materials. Special students, especially those identified as "gifted, " received attention in the form of specific units of study designed to provide enriching and challenging experiences. Curricular materials and suggestions were pragmatic--with emphasis on basic skills and creative ways to meet transescent needs.

As a result of these analyses, an annotated bibliography of sources of information of particular interest to middle school language arts teachers was created and appendixed to the dissertation to provide an easily accessible guide to these articles and documents.

A systematic analysis of articles and documents published for middle school language arts teachers during the years 1980-1983 was conducted in order to determine to what extent the following research questions were being addressed in those publications: (1) What was included within the language arts curriculum for American Middle School students at that time? (2) What innovative programs, teaching approaches and techniques were being used within the language arts curriculum for American Middle Schools? (3) What research had been reported that may have affected the teaching/learning of language arts in American Middle Schools?
Keywords: Education, Language and Literature.